Exploring Innovative Strategies and Action Programs to Accelerate Economic Recovery - Bella Wulan; Zara Fatima (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Rapid and sustainable economic recovery is a crucial challenge amidst global dynamics and continuing uncertainty. This research explores innovative strategies and action programs that can be implemented to accelerate economic recovery. This research methodology involves an in-depth analysis of various economic models that have proven successful in similar situations. It is hoped that the results of this research will provide an in-depth understanding of innovative strategies that can accelerate economic recovery, from fiscal incentives to developing an innovation ecosystem. The proposed action program will include macroeconomic policies, investment in research and development, and empowerment of key sectors in the economy.